Poor and lazy: understanding middle-class perceptions of poverty in China - Xu, M; Walker, R; Yang, L (Routledge, 2021)
Now addressing relative not absolute poverty, China must redistribute income from the middle class to persons experiencing poverty. However, policy rhetoric has recently prioritised laziness as causing poverty, a view widely shared by China’s middle class. Employing a convenience sample of 2,449 middle-class respondents, regressions relate the attribution of poverty to personality, and ideological and individual socialisation. Given two choices, most respondents chose laziness over unfairness but, with more choice, selected ‘modern progress’. Respondents prioritising laziness exhibited extravert and authoritarian personality traits and more faith than others in government policies. They were less well educated and unlikely to have studied social sciences. Respondents subsequently attributing poverty to modern progress had similar characteristics but were not extravert. Building support for redistributive policies could therefore prove difficult.